Dual textured BiVO4/Sb:SnO2 heterostructure for enhanced photoelectrochemical Water-splitting - Jeong, Yoo Jae; Hwang, Sung Won; Chaikasetsin, Settasit; Han, Hyun Soo; Cho, In Sun (Chemical Engineering Journal, 2022)
Heterostructure engineering, combining dissimilar materials into a single substrate, allows the alteration of the optical, electrical, and electrochemical properties of photoelectrodes for photoelectrochemical (PEC) water splitting. Herein, we successfully synthesized a novel dual-textured BiVO4 / Sb:SnO2 heterostructure as a photoanode for PEC water-splitting devices. Sb:SnO2 (ATO) nanorods (NRs) with a [0 0 1] growth orientation were first grown on a fluorine-doped tin oxide substrate by a hydrothermal method. Subsequently, the BiVO4 (BVO) seed layer was deposited on the ATO NRs using a solution spin-coating followed by a second hydrothermal growth to synthesize the dual-textured BVO/ATO heterostructure (dt-BAH). The resultant dt-BAH photoanode was composed of (0 0 1)-textured BVO on the [0 0 1]-oriented single-crystalline ATO NRs, and their interface exhibited intimate junctions. In addition, the textured BVO exhibited two different facets of (0 0 1) and (1 0 1). Notably, the synthesized dt-BAH photoanode showed a considerable enhancement in charge collection performance, resulting in a photocurrent density approximately four times higher than that of the textured BVO grown on the randomly oriented ATO nanoparticle film (single-textured BAH). Our results provide new insights into heterostructure design for the development of efficient photoelectrodes.
Keywords: Bismuth vanadates; Charge collection; Dual-textured; Fluorine doped-tin oxides; Growth orientations; Oxide substrates; Photo-anodes; Photoelectrochemical water splitting; Photoelectrode; Synthesised; Bismuth vanadate; Charge collection; Dual-textured; Heterostructure; Photoelectrochemical water splitting